ISBD : International Standard Bibliographic Description - International Federation Of Library Associations and Institutions. ISBD Review Group; International Federation of Library Associations and Institutions. Cataloguing Section. Standing Committee (Berlin ; Boston : De Gruyter Saur, 2011)
This new edition of the first consolidated ISBD is useful and applicable for descriptions of bibliographic resources in any type of catalogue.
Includes bibliographical references and index.
rua 09/05/13
Loans
Keywords: International Standard Bibliographic Description; Descriptive cataloging -- Standards